Low-Cost Blower-Based Ventilator - Anyarin Thitirattanapong; Salila Ongtrakul; Chuchart Pintavirooj (My University, 2021)
Ventilator has become an intensively important part of medicalhealthcare, especially in this widespread pandemic of COVID-19. The most popular one is an Ambu Bag with a bag valve mask (BVM). This ventilator, however, requires a manual resuscitator to operate its function with a limited air volume inside the bag. During the operation, moreover, it causes the noisy sound due to its mechanism as well. The alternative is using Non-Ambu Bag ventilator. This optional ventilator can regulate using user’s smartphone to command the operation of ventilator with configurable quantity and rate of volume and flow.
Keywords: IoT-based Smart Home Systems; IoT-based Control Systems; Engineering and Technology Innovations